CORPORATE GOVERNANCE AND PROFITABILITY ON EARNINGS MANAGEMENT IN INDONESIAN INFRASTRUCTURE FIRMS: THE ROLE OF LEVERAGE - Agus Hocky; Teddy Chandra; Triyonowati Triyonowati (PT. Anagata Sembagi Education, 2025)
This study investigates the influence of profitability, audit firm size, and the proportion of independent commissioners on earnings management, with leverage as a mediating variable. The research focuses on companies in the infrastructure sector listed on the Indonesia Stock Exchange (IDX) between 2017 and 2022. Employing a managerial balance sheet perspective and structural equation modeling, the study finds that audit firm size, independent commissioners, and leverage significantly affect earnings management. Profitability and audit firm size also influence leverage. Furthermore, leverage mediates the relationship between profitability and earnings management and partially mediates the relationship between audit firm size and earnings management. These findings offer valuable implications for improving corporate governance and enhancing the quality of financial reporting, especially in sectors highly dependent on debt financing.